LAW ENFORCEMENT AGAINST INDIVIDUAL GUARANTEE FOREIGNERS WHO VIOLTES THE CRIME OF IMMIGRATION (CASE STUDY OF AUSTRALIAN CITIZENS: WTH) - Syahrin, M. Alvi; Febrianto, Arief; Sumantri, M. Judo Ramadhan (Polteknik Imigrasi, 2023)
The increase in the traffic of people in and out of the territory of Indonesia is increasing, the threat of crimes that will be committed by foreigners cannot be denied. Foreign Guarantor has an important role in dealing with these threats, so law enforcement must be considered. The DNH case is an example of a case that occurred at the Class I Immigration Office of TPI Cirebon, which is an Australian WTH guarantor who is suspected of abusing his authority as a WTH guarantor. The formulation of the problem consists of What are the factors influencing the implementation of Article 116 of the Immigration Law?; Why is the Guarantor not taken legal action?; What legal remedies can the Cirebon Immigration Office take in the case of WTH and DNH? Normative-empirical legal research using statutory instruments related to Foreign Guarantor and Investigation which is then analyzed with facts in the field. Law enforcement against WTH by investigators has been effective in accordance with the provisions of Articles 71 and 116 of the Immigration Law. DNH has not taken any legal action so that law enforcement needs to be improved. Legal efforts that can be made to the Guarantor are conducting an investigation so that it can be seen that the sanctions that can be given are criminal or administrative, administrative sanctions need to be reviewed.